Antibiotic prescribing for acute uncomplicated cystitis in Lebanese community pharmacies using a simulated patient - Yaacoub SG; Koyess V; Lahoud N; Rahme D; Francis N; Saleh N; Maison P (Centro de Investigaciones y Publicaciones Farmaceuticas, 2019)
Background: Urinary tract infections are considered as one of the most frequent bacterial infections in the community and hospital settings. In this era of increasing antimicrobial resistance, antimicrobial stewardship has become highly important in the struggle to preserve the effectiveness of available drugs. One the main causes of antibiotic resistance is the inappropriate prescribing of antibiotics; which evidence show that community pharmacists contribute to. Objective: This study aims to evaluate antibiotic prescribing rate and responses of the contact persons in community pharmacies and to assess the conformity of the prescribed antibiotics with international guidelines. It also aims to evaluate the responses with sociodemographic characteristics. Methods: A cross-sectional, nationwide study conducted between February and May 2017 using a simulated patient case of acute uncomplicated cystitis. Two hundred fifty pharmacies were included. Descriptive data was reported for the medications prescribed, conformity, questions asked and counseling. Bivariate analysis using the Pearson chi-squared, Fisher's exact and Student's t-tests were used to identify possible factors affecting the prescribing rates and responses in community pharmacies. Results: The prescribing rate of antibiotics was 83.6% (n=209) with ciprofloxacin being the most prescribed (50.2%, n=105). The global conformity to international guidelines was 3.8% (n=8) with the highest conformity rate for the antibiotic choice (91.4%, n=191). Counseling about what to do in case symptoms persist was 12.8% (n=32) and that of non-pharmacological management was 53.6% (n=134). Male participants (88.1%) had a higher prescribing rate than female participants (77.6%) (p<0.05). The number of questions asked was higher in pharmacists and in female participants (p<0.05). Other results showed non-significant differences in diagnosis, antibiotic prescribing, conformity rates, referral rates and counseling points between the pharmacists and assistants. Conclusions: The high antibiotic prescribing rate in Lebanese community pharmacies is alarming and calls for action. This should be tackled by legislative bodies, which should enforce laws that restrict such practices.